2021
DOI: 10.1111/papr.13063
|View full text |Cite
|
Sign up to set email alerts
|

A paramedian approach for dorsal root ganglion stimulation placement developed to limit lead migration and fracture

Abstract: Introduction: Dorsal root ganglion stimulation (DRG-S), has demonstrated superiority in the treatment of complex regional pain syndrome and causalgia. Lead migration and fracture impact DRG-S therapeutic stability. Lead anchoring reduces DRG-S lead migration without increasing lead fracture. Lead fracture may be related to lead entrapment in the superficial fascial plane. A novel medialized approach for lead placement and anchoring is presented to address these issues. Methods:We suggest an alternative techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Initially, anchoring was not recommended due to the risk of fracture, but a recent update in the literature now supports the use of anchoring in addition to an S-shape loop in the epidural space for strain relief. [55] Success rate is high in majority of studies with one notable exception [56]. Patients demonstrated improved QOL and a decrease in consumption of analgesics including opioids [51].…”
Section: Dorsal Root Ganglion Stimulationmentioning
confidence: 99%
“…Initially, anchoring was not recommended due to the risk of fracture, but a recent update in the literature now supports the use of anchoring in addition to an S-shape loop in the epidural space for strain relief. [55] Success rate is high in majority of studies with one notable exception [56]. Patients demonstrated improved QOL and a decrease in consumption of analgesics including opioids [51].…”
Section: Dorsal Root Ganglion Stimulationmentioning
confidence: 99%
“…Anchoring the 1-mm DRG-S lead has proven to be an integral step in decreasing lead migration and potentially lead fracture [ 2 ]. Additionally, an ipsilateral, paramedian approach for thoracolumbar DRG-S lead placement was described to decrease lead fracture and enable an alternative technique to the wider-angled contralateral approach [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia for placement of a trial or permanent DRG device has evolved since the early cases were performed. Recognition of the sensitivity of the DRG to mechanical stimuli during placement has led to raised awareness of anesthetic management and the procedural approach [ 3 , 11–13 ]. Insult to neural structures can cause a neuritis, paresthesia, or weakness, and although commonly self-limiting, longer-term injuries during lead placement in asleep, unmonitored patients have been reported [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Many studies reported that fracture was the most common trigger of CRPS I. [10][11][12] Jellad et al 13 reported that CRPS I occurred in 32.2% of distal radius fracture patients. The injury mechanism of distal radius fractures was similar to radial head fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that fracture was the most common trigger of CRPS I. 10 , 11 , 12 Jellad et al . 13 reported that CRPS I occurred in 32.2% of distal radius fracture patients.…”
Section: Introductionmentioning
confidence: 99%